Observation of GEO Satellite above Thailand's Sky - K. Kasonsuwan (2018)
© Published under licence by IOP Publishing Ltd. The direct observations of Geostationary Orbit (GEO) satellites above Thailand's sky by 0.7-meters telescope were proceeded at Inthanon Mt., Chiang Mai, Thailand. The observation took place at night with Sidereal Stare Mode (SSM). With this observing mode, the moving object will appear as a streak. The star identification for image calibration is based on (1) a star catalogue, (2) the streak detection of the satellite using the software and (3) the extraction of the celestial coordinate of the satellite as a predicted position. Finally, the orbital elements for GEO satellites were calculated.